Sudden cardiac arrest accompanied by severe accidental hypothermia - modifications of the standard cardiopulmonary resuscitation procedure - Czyż, Rafał; Leśkiewicz, Marcin; Czyż, Patrycja (Journal of Education, Health and Sport, 2018)
Severe accidental hypothermia is associated with a high mortality rate. This is related to the fact that assessment and treatment may be difficult: the severity of determining the presence of pulse and breathing, the significant sensitivity of the patient to a change in body position, difficulty in the instrumental protection of airways, ease of ventricular fibrillation occurrence and many other risks. A well-prepared medical team, coordinated actions based on current medical guidelines and recommendations, give a chance to save patients even after a few hours of cardiopulmonary resuscitation. Despite the availability of advanced devices for heating and supporting cardiovascular function in patients with cardiac arrest with coexisting hypothermia, basic activities such as isolation and protection against heat loss are critical important rescue tasks necessary for effective treatment of the patient. In connection with the above, this article summarizes current information about sudden cardiac arrest with coexisting hypothermia. The following aspects were discussed: definition, epidemiology, diagnosis and assessment of hypothermia severity and modifications of standard resuscitation algorithm in the case of coexisting hypothermia.